A demonstration of anion templation and selectivity in pseudorotaxane formation - Wisner, J; Beer, P; Drew, M (2001)
First- and second-sphere coordination of a chloride anion templates the formation of a [2]pseudorotaxane (see picture) in which a pyridinium diamide threads through the annulus of a macrocyclic isophthalamide wheel. The formation of the pseudorotaxane depends on the nature of the anion involved: the use of a larger anion destabilizes the entire recognition motif.